2005
DOI: 10.1016/j.bbamcr.2005.04.012
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin signaling and regulation of cyclin D1 promoter in NRK-49F cells transformed by down-regulation of the tumor suppressor lysyl oxidase

Abstract: Lysyl oxidase is the enzyme that is essential for collagen and elastin cross-linking. Previous investigations showed that lysyl oxidase is down-regulated in many human tumors and ras-transformed cells. Recently, we proved that antisense down-regulation of lysyl oxidase in NRK-49F cells induced phenotypic changes and oncogenic transformation, characterized by p21(ras) activation and beta-catenin/cyclin D1 up-regulation. In the present paper, we examined beta-catenin intracellular distribution and its associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…These results point to a unique mechanism of regulation of carcinoma progression involving LOXL proteins [69,70]. Giampuzzi et al [71] reported the oncogenic transformation of normal rat kidney fibroblasts (NRK-49F) by transfecting with antisense LOX cDNA [71]. β-Catenin was upregulated as was cyclinD1 while the ras oncogene became activated in response to the downregulation of LOX in these cells.…”
Section: Oncogenic Cellular Transformationmentioning
confidence: 93%
“…These results point to a unique mechanism of regulation of carcinoma progression involving LOXL proteins [69,70]. Giampuzzi et al [71] reported the oncogenic transformation of normal rat kidney fibroblasts (NRK-49F) by transfecting with antisense LOX cDNA [71]. β-Catenin was upregulated as was cyclinD1 while the ras oncogene became activated in response to the downregulation of LOX in these cells.…”
Section: Oncogenic Cellular Transformationmentioning
confidence: 93%
“…Recent reports have demonstrated novel roles for LOX, including its involvement in motility and migration in fibroblasts (50) and regulation of cell adhesion (20). In addition, LOX expression and activity have been observed in the cytoplasm and nucleus (29) and implicated in cell signaling and transcriptional gene regulation, as evidenced by the activation of the collagen III ␣ 1 -promoter through LOX-induced binding of Ku antigen (18).…”
Section: The Lox Enzymementioning
confidence: 99%
“…Previous reports have shown that genetic inhibition of LOX increases cell proliferation, again supporting the idea that LOX acts as a tumor suppressor. Mechanistically, LOX is thought to affect fibroblast proliferation through elevated cyclin D1, as antisense down-regulation of LOX in rat kidney fibroblasts increases cyclin D1 expression through hcatenin signaling (11). Recently, it was reported that it is the COOH-terminal propeptide region of LOX that acts intracellularly to suppress transformation of fibroblast by Ras (12).…”
Section: Lox Is Essential For Hypoxia-induced Metastasismentioning
confidence: 99%